Trigger Factor-Mediated Prolyl Isomerization Influences Maturation of the Streptococcus pyogenes Cysteine Protease - Lyon, William R. (American Society for Microbiology, 2003)
Trigger factor, a ribosome-associated chaperone and peptidyl-prolyl cis-trans isomerase (PPIase), is essential for the secretion and maturation of the cysteine protease of the pathogenic gram-positive bacterium Streptococcus pyogenes. In the absence of trigger factor, the nascent protease polypeptide is not targeted to the secretory pathway. Some partial-function mutations restore targeting. However, the secreted protease does not efficiently mature into an enzymatically active form, suggesting that trigger factor has an additional role in protease biogenesis. Here, we show that, while not required for targeting, the PPIase activity of trigger factor is essential for maturation of the protease following its secretion from the bacterial cell. Site-specific mutations introduced into ropA, the gene which encodes trigger factor in S. pyogenes, produced mutant proteins deficient in PPIase activity. When these mutant alleles were used to replace the wild-type gene on the streptococcal chromosome, analysis of protease biogenesis revealed that, although the protease was secreted normally, it did not efficiently mature to an active form. Furthermore, mutation of a single proline residue in the protease prodomain suppressed the requirement for PPIase activity, suggesting that this residue is the target of trigger factor. These data support a model in which trigger factor-mediated prolyl isomerization influences the conformation of the prodomain, which in turn directs the protease into one of several alternative folding pathways.